High-Altitude Living Shapes the Skin Microbiome in Humans and Pigs - Zeng, Bo; Zhao, Jiangchao; Guo, Wei; Zhang, Siyuan; Hua, Yutong; Tang, Jingsi; Kong, Fanli; Yang, Xuewu; Fu, Lizhi; Liao, Kun; Yu, Xianqiong; Chen, Guohong; et al. (Frontiers in Microbiology, 2017)
While the skin microbiome has been shown to play important roles in health and disease in several species, the effects of altitude on the skin microbiome and how high-altitude skin microbiomes may be associated with health and disease states remains largely unknown. Using 16S rRNA marker gene sequencing, we characterized the skin microbiomes of people from two racial groups (the Tibetans and the Hans) and of three local pig breeds (Tibetan pig, Rongchang pig, and Qingyu pig) at high and low altitudes. The skin microbial communities of low-altitude pigs and humans were distinct from those of high-altitude pigs and humans, with five bacterial taxa (Arthrobacter, Paenibacillus, Carnobacterium, and two unclassified genera in families Cellulomonadaceae and Xanthomonadaceae) consistently enriched in both pigs and humans at high altitude. Alpha diversity was also significantly lower in skin samples collected from individuals living at high altitude compared to individuals at low altitude. Several of the taxa unique to high-altitude humans and pigs are known extremophiles adapted to harsh environments such as those found at high altitude. Altogether our data reveal that altitude has a significant effect on the skin microbiome of pigs and humans.